2021
DOI: 10.1111/ped.14454
|View full text |Cite
|
Sign up to set email alerts
|

Ampicillin‐sulbactam monotherapy in infants with febrile urinary tract infections

Abstract: Background: Cephalosporin is the most commonly used empirical agent for urinary tract infections (UTIs) in children. However, increasing use of cephalosporins can lead to an increase in resistant pathogens. This study therefore aims to investigate the effects of monotherapy with ampicillin-sulbactam as an alternative to cephalosporins. Methods: All 2-to 24-month-old patients who were hospitalized at Pusan National University Children's Hospital due to a first episode of a febrile UTI during the 2-year period f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A total of 4 studies contained older children, and authors were unable to provide data specific to those <2 months of age. 7,10,31,32 Finally, 1 study was only published as an abstract without any outcome data. 33 Studies were published between 1978 and 2020 (Table 1) and reported on a median sample size of 143.5 (range: 12-3973) participants per study.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A total of 4 studies contained older children, and authors were unable to provide data specific to those <2 months of age. 7,10,31,32 Finally, 1 study was only published as an abstract without any outcome data. 33 Studies were published between 1978 and 2020 (Table 1) and reported on a median sample size of 143.5 (range: 12-3973) participants per study.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%